Tearing the World Apart : Bob Dylan and the Twenty-First Century - Hoffman, Eric R.; Goss, Nina (Book collections on Project MUSE., 2017)
Tearing the World Apart participates in the creation of the postmillennial Bob Dylan by exploring three central records of the twenty-first century--"Love and Theft" (2001), Modern Times (2006), and Tempest (2012)--along with the 2003 film Masked and Anonymous, which Dylan helped write and in which he appears as an actor and musical performer. The collection of essays does justice to this difficult Bob Dylan by examining his method and effects through a disparate set of viewpoints. Readers will find a variety of critical contexts and cultural perspectives as well as a range of experiences as members of Dylan's audience. The essays in Tearing the World Apart illuminate, as a prism might, its intransigent subject from enticing and intersecting angles. --Publisher description.